Pertumbuhan Vegetatif Tanaman Jambu Kristal (Psidium guajava L.) di Tabulampot dengan Pemberian Pupuk NPK dan Komposisi Media Tanam - Mego, Petrus Pance; Rosawanti, Pienyani; Hidayati, Nurul (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2025)
This study aims to evaluate the growth response of crystal guava (Psidium guajava L.) plants to the application of NPK 16-16-16 fertilizer doses and types of planting media in sandy soil. The study was conducted for five months (August 2024–January 2025) at Campus III Land, Muhammadiyah University of Palangka Raya. The method used was a two-factor Randomized Block Design (RAK) Factorial with four replications. The first factor was the dose of NPK fertilizer (10, 20, 30, and 40 g/plant), and the second factor was the planting media (soil + manure + sawdust and soil + manure + rice husk charcoal). The parameters observed included plant height, number of leaves, and stem diameter. The results showed that the administration of NPK 16-16-16 had a very significant effect on the three growth parameters. The optimal dose for plant height and stem diameter was 20 g/plant, while the optimal number of leaves was at a dose of 40 g/plant. Rice husk charcoal planting media gave better results than sawdust. There was no interaction between fertilizer and planting media on all